Recent Advances in the Development of Noble Metal NPs for Cancer Therapy - Rui Zhao; Jia Xiang; Bo Wang; Lin Chen; Songwen Tan (Bioinorganic Chemistry and Applications)
With the development of nanotechnology, noble metal nanoparticles are widely used in the treatment of cancer due to their unique optical properties, excellent biocompatibility, surface effects, and small size effects. In recent years, researchers have designed and synthesized a large number of nanomedicines that can be used for cancer treatment based on the morphology, physical and chemical properties, mechanism of action, and toxicological studies of noble metal nanoparticles. Furthermore, the integration of diagnosis and treatment, hyperthermia, cytotoxicity research, and drug delivery system based on the study of noble metal nanoparticles can be used as effective means for cancer treatment. This article focuses on the analysis of noble metal nanoparticles that are widely used in the treatment of cancer, such as gold nanoparticles, silver nanoparticles, platinum nanoparticles, and palladium nanoparticles. The various methods and mechanisms of action of noble metal nanoparticles in the treatment of cancer are objectively summarized in detail. Based on the research on the therapeutic safety and toxicity of noble metal nanoparticles, the development prospect of noble metal nanoparticles in the future clinical application is prospected.